An Analysis of Speech Error made by Character Dory in “Finding Dory” Movie - Refina Wati; Zulkhaeriyah Zulkhaeriyah; Dede Rosyadi ZA (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The purpose of this study is to analyze the types and factors of speech errors that uttered by character Dory in “Finding Dory” movie. This study used descriptive qualitative approach. The source of the data is “Finding Dory” movie. Furthermore, the data was collected through watched and transcribed the utterances of Dory that indicate the speech errors. In total there are 90 data of speech errors that identified and classified based on Clark & Clark’s (1977) theory into eight types. Those are predominantly categorized as repeats with total 30 data, followed by silent pauses with 25 data, filled pause with 12 data, interjection with 9 data, unretraced false starts 5 data, retraced false starts 4 data, stutters 3 data, and correction with 2 data. The speech error in Dory’s utterances is mostly influenced by her cognitive cognition.